2013
DOI: 10.1039/c3ob40891d
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-catalyzed asymmetric ring-opening of azabicyclic alkenes with alcohols

Abstract: A novel asymmetric ring-opening reaction of N-substituted azabenzonorbornadienes with a wide variety of substituted benzyl alcohols and the addition reaction of N-substituted azabenzonorbornadienes with thiols are reported, affording the corresponding 1,2-trans-alkoxyamino products in moderate yields with excellent enantioselectivities (up to 94% ee) and the corresponding thiol addition products in high yields with lower enantiomeric excesses (ee) in the presence of iridium catalyst, respectively. The effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…Therefore, among the ligands screened, achiral ligand DPPF was the most effective one in terms of yield, which afforded 3aa in 94% yield within 4 hours (entry 3). The impact of the amount of catalyst loading on the reaction was then investigated (entries [13][14][15][16], and it was observed that the yield of 3aa was strongly influenced by the amount of catalyst loading. The yield of 3aa increased as the amount of catalyst loading gradually increased to 1.5 mol% (entries 3, 13, 14), and the best yield could be obtained in the presence of 1.5 mol% of [Ir(COD)Cl] 2 with 3.0 mol% DPPF (entry 3).…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…Therefore, among the ligands screened, achiral ligand DPPF was the most effective one in terms of yield, which afforded 3aa in 94% yield within 4 hours (entry 3). The impact of the amount of catalyst loading on the reaction was then investigated (entries [13][14][15][16], and it was observed that the yield of 3aa was strongly influenced by the amount of catalyst loading. The yield of 3aa increased as the amount of catalyst loading gradually increased to 1.5 mol% (entries 3, 13, 14), and the best yield could be obtained in the presence of 1.5 mol% of [Ir(COD)Cl] 2 with 3.0 mol% DPPF (entry 3).…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…As azabenzonorbornadienes are less reactive than the corresponding oxabenzonorbornadienes,, this kind of reaction was mainly focused on the oxabenzonorbornadienes. Although amines have been successfully applied,, the development of efficient catalytic system for the asymmetric ring opening reactions of azabenzonorbornadienes with other heteronucleophiles is necessary . Our group has a continuous interest in the asymmetric ring opening reactions of oxa‐/azabenzonorbornadienes and has applied terminal alkynes, phenols, and amines as suitable nucleophiles using the strategy of combination of transition metal complexes with Lewis acids as co‐catalytic systems.…”
Section: Screening Of Chiral Ligands[a]mentioning
confidence: 99%
“…However, bulky steric hindrance in nucleophiles seemed necessary to ensure high enantioselectivities. Catalyzed by iridium complexes, the ARO reactions of azabenzonorbornadienes with alcohols and phenols were also reported, but the results were not satisfactory due to low to moderate ee’s obtained in many cases. The development of new and efficient catalysts or catalytic systems for ARO reactions of azabenzonorbornadienes is still interesting and necessary.…”
mentioning
confidence: 90%